Daily Service Activity of Inner Guard Officer in the Russian Empire in the Middle of 19th Century - P. A. Kolpakov (Научный диалог)
The aims of this article are: (1) delineation of the categories of “casual” and “normal” based on the results of the study of archival materials documenting the daily activities of the Internal guard troops, particularly their disciplinary and legal violations; (2) identification of the characteristics of the daily activities of the internal troops of the Russian Empire in the following areas: staffing the army, maintenance of public order, officers’ interpersonal relations. To achieve the said goals, the methods of historical research are used: systemic and narrative. The author claims that minor breaches of the discipline and regulations by military personnel of Separate corps of Internal guards were everyday in nature, but the recurrence did not legalize them, that is they did non become the norm of behaviour. The activity of the Inner guard in ensuring public order, restriction of access of citizens to drinking establishments could bring losses to the owners of such establishments. It is noteworthy that abuse of authority by an officer of the Inner guard (Lieutenant Strizhevsky) in the implementation of such actions was suppressed only by military and civil authorities at the level of the governorate. The everyday nature of the practice of evasion of the population from military service through the conclusion of an unintended legal agreements with the officers who carried out the recruitment were noted. The interaction between the commanders of the internal troops of awareness on the personal qualities of military personnel, transferring from unit to unit, was identified.